Clustering of the Russian regions by information and communication technologies indicators – infrastructure and Internet access - N. V. Kuznetsov; T. A. Pershina; A. A. Sychev; A. S. Savostitsky (Вестник университета)
In the context of the digitalization of the economy, it is important to systematize indicators that will fully assess the work of the regions of the Russian Federation in the direction of the country’s information development. The article presents a system for assessing state entities within the framework of infrastructure and access to the Internet network throughout the country. The authors analyze the heterogeneity of the regional structure of Russia in terms of digitalization indicators. The use of advanced statistical parametric and non-parametric methods made it possible to determine the stratification of regions. The paper compares the level of development of information and communication technologies in groups (layers) of regions according to the indicators included in the block “information and communication technologies infrastructure and access”, obtained as a result of monitoring the development of the information society in the Russian Federation. Researchers conduct a factor analysis to identify the main components that affect the level of development of information and communication technologies in the Russian regions.